Pengaruh Motivasi, Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja serta Dampaknya pada Kinerja Karyawan - Jauharun Niam; Tantri Yanuar Rahmat Syah (OPSI, 2019)
Changes in leaders in an organization are common and will affect all units from the management level to implementation. This is related to the leadership style and organizational culture developed by new leaders, especially in terms of motivating and providing job satisfaction in achieving the best performance. This research is explanatory research that proves a causal relationship between work motivation, transformational leadership, organizational culture, and employee job satisfaction as a mediating variable on employee performance. The study also aims to see whether or not two or more variables have a relationship, and how significant the relationship is and how the relationship is going. In this study, to analyze and find out the significant level, and the relationship between variables, the structural equation model analysis method is used. The results of the study on 385 respondents who were a sample of research in educational foundations that shelter educational institutions from early childhood education to university level that are spread in almost all regions of Indonesia showed the need for special attention to work motivation which did not significantly influence job satisfaction and satisfaction work does not mediate employee performance against motivation, leadership, and organizational culture variables. Other results indicate that the variables of work motivation, organizational culture, and transformational leaders significantly influence employee performance.